Unveiling the role of filler surface energy in enhancing thermal conductivity and mechanical properties of thermal interface materials. (June 2022) - Ma, Qiangqiang; Wang, Zhenyu; Liang, Ting; Su, Yunpeng; Li, Junhong; Yao, Yimin; Zeng, Xiangliang; Pang, Yunsong; Han, Meng; Zeng, Xiaoliang; Xu, Jianbin; Ren, Linlin; et al.
Graphical abstract: Abstract: With heat-flux density of electronics drastically increase polymer-based thermal interface materials play a critical role in the performance of electronics. Although surface energy of fillers has been recognized as a crucial parameter, the exploitation of the filler surface energy-dependent properties is still unclear. Herein, we report on unveiling the effect of the surface energy of aluminum on thermal and mechanical properties in thermal interface materials consisted of polydimethylsiloxane and modified aluminum with silane-coupling agents containing varied chain lengths. The results show that reducing the surface energy of aluminum is beneficial to improve the aluminum fillers dispersibility in polydimethylsiloxane, leading to improved macroscopic properties, including rheology, mechanical properties, and thermal properties. Furthermore, based on the thermodynamic prediction, a winding hypothesis was proposed to explain the interaction between the modified aluminum and polydimethylsiloxane. This work provides valuable guidance for rationally designing the surface energy of fillers in thermal interface materials.